2011
DOI: 10.1113/expphysiol.2011.060178
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced oxidative-nitrosative stress is associated with impaired dynamic cerebral autoregulation and blood-brain barrier leakage

Abstract: The present study examined whether dynamic cerebral autoregulation and blood-brain barrier function would become compromised as a result of exercise-induced oxidative-nitrosative stress. Eight healthy men were examined at rest and after an incremental bout of semi-recumbent cycling exercise to exhaustion. Changes in a dynamic cerebral autoregulation index were determined during recovery from continuous recordings of blood flow velocity in the middle cerebral artery (MCAv) and mean arterial pressure during tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 62 publications
(86 reference statements)
2
68
0
Order By: Relevance
“…In addition to the deleterious consequences associated with cerebral hypoperfusion, an inability to buffer spontaneous surges in MAP such as that encountered during intense (boxing) exercise has the potential to cause cerebral hyperperfusion and BBB (blood-brain barrier) disruption, ultimately resulting in capillary stress failure [39], events that are further compounded by cerebral hypoxaemia [54,55]. This may prove to be the common mechanism underlying the systemic extravasation of the BBBspecific protein S100β [53], punctate micro-haemorrhages [56] and neuropathological lesions [41] that have previously been reported in more advanced cases of CTBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the deleterious consequences associated with cerebral hypoperfusion, an inability to buffer spontaneous surges in MAP such as that encountered during intense (boxing) exercise has the potential to cause cerebral hyperperfusion and BBB (blood-brain barrier) disruption, ultimately resulting in capillary stress failure [39], events that are further compounded by cerebral hypoxaemia [54,55]. This may prove to be the common mechanism underlying the systemic extravasation of the BBBspecific protein S100β [53], punctate micro-haemorrhages [56] and neuropathological lesions [41] that have previously been reported in more advanced cases of CTBI.…”
Section: Discussionmentioning
confidence: 99%
“…The initial workload was set at 35 W for 5 min (70 rev./min) and increased by 35 W · min − 1 until volitional exhaustion as described previously [39]. Expired gas fractions were measured using fast responding paramagnetic oxygen (O 2 ) and IR CO 2 analysers (Servomex 1400 Series Analyser).…”
Section: Peak Aerobic Power Testmentioning
confidence: 99%
“…Importantly, tightness of the BBB is reduced by increases in both cerebral perfusion pressure (27) and circulating interleukin-6 levels (162), two changes occurring during dynamic exercise (188). High-intensity exercise has been found to increase the permeability of the BBB without causing structural damage (16), strongly suggesting that during exercise, circulating factors may become important regulators of cerebrovascular tone and neuronal function. But this still needs to be demonstrated.…”
Section: Mechanisms Of Exercise-dependent Maintenance Of Cerebrovascumentioning
confidence: 99%
“…83,84 Unless countered by the neuroprotective influences of sympathetic activation or cerebral autoregulation (CA; see later), this potentially increases the risk of hyperperfusion injury predisposing to stroke or blood-brain barrier (BBB) breakthrough. 85 This risk has been well publicized in the media in the United Kingdom recently, due to a high-profile clinical case of a BBC journalist claiming that the stroke suffered was caused by 'HIT' while exercising on a rowing ergometer. 86,87 While certainty about cause-and-effect is difficult to establish, a clinical case study such as this highlights the potential safety issues associated with the HIT paradigm for the brain.…”
Section: Does High-intensity Interval Exercise Training Pose a Dangermentioning
confidence: 99%
“…Furthermore, intense exercise can increase BBB permeability subsequent to a free radical-mediated impairment in CA, rendering the brain more susceptible to overperfusion and extracellular (vasogenic) edema; which has been shown to occur even in response to a more graduated incremental exercise test to exhaustion. 85 The direct effect of sympathetic nervous activity (SNA) on the cerebrovasculature remains controversial 28,105,106 and is further complicated in humans by the common inference of global SNA measures reflecting cerebral effects (e.g., via microneurography of SNA in the peroneal nerve versus noradrenaline spillover measurements 107 ). In fact, studies in sheep have indicated an inverse relationship between global and cerebral SNA; 108,109 thus, increases in muscle SNA may be reflected in a lowering of cerebral SNA.…”
Section: Optimizing Cerebrovascular Adaptation and Safety For High-inmentioning
confidence: 99%